Поняття ідіолекту в українському політичному дискурсі - Деренчук, Наталія; Derenchuk, Nataliya (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті розглянуто проблему витлумачення ідіолекту в українському політичному дискурсі. На матеріалі публічних виступів українських політиків П. Порошенка та А. Яценюка проаналізовано спільні та відмінні лексико-граматичні і прагмастилістичні особливості їхніх ідіолектів, які індивідуалізують мовлення, сприяють забезпеченню зв’язку з аудиторією. The article deals with the problem of determining of idiolect and outlines its place in the Ukrainian political discourse. It is established that this term refers to the language (or some its part or aspect) with certain parameters (phonological, semantic, lexical, syntactic, etc) that can be characterized in terms of individual or collective properties. It was found that a comprehensive study of this issue is realized by reference to language and verbal behavior of a particular political figure. Characteristics of its major components over a significant period of time allows to make its integrated linguistic portrait. It is analyzed distinctive and common syntactic, stylistic and linguistic pragmatic features of the idiolect of Ukrainian political leaders on the material of public speaking of P. Poroshenko and A. Yatsenyuk. The use of specific syntactic structures and stylistic devices combined with brilliant oratorical abilities doubles effect of rhetorical techniques.
The Concept of Idiolect in Ukrainian Political Discourse
Keywords: політичний дискурс; політична мова; мовна особистість; ідіолект; індивідуальний стиль; political discourse; linguistic identity; political speech; idiolect; individual style